Ethnoscience: A Philosophical Study with Anthropological, Ontological and Axiological Perspectives - Amiruddin, Mohd Zaidi Bin; Nahadi, Nahadi; Anwar, Sjaeful; Samsudin, Achmad; Suhandi, Andi; Aminudin, Adam Hadiana (Vidya Karya, 2024)
One of the emerging scientific developments is science-based local wisdom, or "ethnoscience." This research examines the urgency of ethnoscience when viewed from a philosophical perspective with an anthropological, ontological, and axiological perspective approach. This research uses a library research method with relevant sources related to the studied topic, such as books, scientific articles, and other relevant sources. The results of this study present how critical philosophical studies are to a science that is being developed, especially those that involve community culture. In addition, anthropological, ontological, and axiological perspectives provide an idea of a point of view that not only always refers to the research process but also the need to pay attention to the norms and values of the local culture. That way, future research related to ethnoscience has excellent potential to continue to be carried out through rational considerations and benefit science, culture, society, and the nation.